2015
DOI: 10.1186/s13075-015-0848-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis by platelets in systemic sclerosis patients

Abstract: IntroductionSystemic sclerosis (SSc) is a chronic autoimmune disease characterized by microvascular damage, inflammation, and fibrosis. It has become increasingly evident that platelets, beyond regulating hemostasis, are important in inflammation and innate immunity. Platelets may be an important source of proinflammatory and profibrotic cytokines in the vascular microenvironment. In this study, we sought to assess the contribution of platelet-derived factors in patients with SSc to the angiogenesis of human d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…Plasma 5-HT content is increased in SSc has been reported (81). Another study revealed that intraplatelet 5-HT content is decreased in patients with diffuse SSc compared with that in patients with limited SSc and normal individuals (82). This indicates that the type of SSc also affects the distribution of 5-HT.…”
Section: Systemic Sclerosis (Ssc)mentioning
confidence: 76%
“…Plasma 5-HT content is increased in SSc has been reported (81). Another study revealed that intraplatelet 5-HT content is decreased in patients with diffuse SSc compared with that in patients with limited SSc and normal individuals (82). This indicates that the type of SSc also affects the distribution of 5-HT.…”
Section: Systemic Sclerosis (Ssc)mentioning
confidence: 76%
“…The isoform production switch, altering the ratio of VEGF-A xxx a to VEGF-A xxx b, could be viewed as a contributor to disease, or as a protective response of the ATII and other cells, a regulatory mechanism to maintain homeostasis as we have previously postulated in the lung (10) and others in systemic sclerosis (52,53). Interestingly, it has become clear that IPF is associated with multiple splicing changes, such as that required for VEGF-A 165 b (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are an important source of circulating panVEGF-A in SSc [91] and recent investigation has also proven them to be an important source of VEGF-A165b [92]. Furthermore, tubule formation by dermal MVEC in vitro is impaired when incubated with SSc platelet releasate [92] potentially due to the antiangiogenic action of VEGF-A165b. It is not known whether the platelet load of VEGF-Axxxa/xxxb isoforms remains consistently elevated in SSc or whether isoform switching occurs at some stage in the disease course.…”
Section: What Is the Potential Cellular Source Of Vegf-a Isoforms In mentioning
confidence: 99%
“…Figure 3 demonstrates the pathway of hypoxia induced VEGF-A induction via HIF and hypoxia mRNA stabilization [32,43,53,104]. Known cellular sources of VEGF-A in SSc are illustrated based on available evidence (panVEGF-A = (a), VEGF-A165b = (b)) [11,12,89,91,92,103,111,114,131]. *TGFβ and HIF1α synergistically increase VEGF-A in endothelial cells [104].…”
Section: Figure Legendsmentioning
confidence: 99%